PENGARUH TEKANAN WAKTU, TINDAKAN SUPERVISI, PROSEDUR REVIEW DAN KONTROL KUALITAS, DAN KOMITMEN PROFESIONAL TERHADAP PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT (Studi Empiris pada BPKP Perwakilan Riau dan Sumatera Utara) - F. Sitorus, Marina; Anugerah, Rita; Alamsyah, Mudrika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The objectives of this study is to examine analyze the influence of time pressure, supervision action, review procedure and quality control and professional commitment on the premature sign off audit procedures. The population of this study are 235 auditors, who have worked for BPKP in Riau and North Sumatera. Meanwhile the sample of this research are 115 auditors. The sampling technique used purposive sampling method. Number of questionnaires were distributed by 115 questionnaire. However, the back and can be used for further analysis by 100 questionnaires. The data processed by using SPSS (Statistical Product Service Solution) 21 version software and the data were analyzed to test the hypothesis using multiple linear regression analysis approach.The results of this study indicates that the time pressure have effects on premature sign off with significant 0,000 < 0,05, supervision action have effects on premature sign off with significant 0,018 < 0,05, and review procedure and quality control have significant effect on premature sign off audit procedureshave effects on premature sign off with significant 0,002 <0,05 , but proffesional commitments do not have significant effect on premature sign off audit procedure with significant 0,495> 0,05.Keyword : Time Pressure, Supervision Action, review procedure and quality control, professional commitment, premature sign off